Enabling environment dynamics for scaling digital agriculture: Institutional, policy, and user perspectives on Rwanda’s Smart Nkunganire System (SNS - Kihiu, E.; Kirui, L.; Kayumba, J.; Mudereri, B.T.; Benimana, G.; Gatto, M.; Kihoro, E.; Cyamweshi, A.; Gatari, E. (2025)
This report analyzes the enabling environment for scaling Rwanda’s Smart Nkunganire System (SNS), a national digital platform that modernizes the delivery of subsidized agricultural inputs. Using the CGIAR Innovation Packages and Scaling Readiness framework, the study examines institutional, policy, financial, and user-level factors shaping SNS performance. Findings show that strong political backing, effective public–private partnerships, and growing digital infrastructure have enabled SNS to scale nationally, improving transparency and access to seeds and fertilizers for millions of farmers. However, challenges remain related to connectivity, digital literacy, inclusion of vulnerable groups, and long-term financial sustainability. The report highlights priority actions to strengthen governance, system integration, inclusive design, and data governance to support responsible and sustainable scaling of digital agriculture in Rwanda.